PELAKSANAAN PERJANJIAN ANTARA PDAM KOTA PAYAKUMBUH DENGAN PAMSIMAS KOTA PAYAKUMBUH - Darda Pasmatuti (JCH (Jurnal Cendekia Hukum), 2019)
Water is a very basic need for humans, so in accordance with article 33 paragraph (3) of the 1945 Constitution, natural resources in the form of water must be managed and utilized as well as possible, the formulation of the problem was: with PAMSIMAS Payakumbuh City, What are the obstacles in implementing the agreement and what are the efforts to overcome the obstacles in implementing the agreement between the PDAM and PAMSIMAS ?, The research method was empirical juridical. The results showed that the implementation of the Agreement between Payakumbuh City PDAM and Payakumbuh City PAMSIMAS was implemented based on the Agreement that had been agreed upon by the two parties. The constraints in implementing the agreement were as follows: There was a delay in payment by the PAMSIMAS to the PDAM. Efforts made to overcome the obstacles in the implementation of the agreement between the PDAM and PAMSIMAS are by way of the two parties agreeing to settle by deliberating and consensus. In the event of a delay in payments by PAMSIMAS, the PDAM gives sanctions in the form of fines. The author's advice was: To implement the Agreement between Payakumbuh Municipal PDAM and Payakumbuh City PAMSIMAS as well as possible, pay water bill bills on time, so that PDAM Kota Payakumbuh's efforts in facing existing constraints, the implementation needs to be increased so that a balanced relationship is created with the Payakumbuh Municipal PDAM.